PENGELOLAAN PENGELUARAN KAS OPERASIONAL PERUSAHAAN PT. CITRA WARNA JAYA ABADI PADA MASA PANDEMI COVID 19 - Ni Luh Putu Sandrya Dewi; Ni Putu Ayu Mirah Mariati; I Wayan Sudiarsa; Ni Putu Sri Dewi Eka Pujiani (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
Petty cash or commonly referred to as petty cash is a number of funds that are specifically designated as expenses that are relatively small in number and nature. Petty cash is usually used to finance the company's operations or other matters related to the activities carried out by the company. The establishment of a petty cash fund is part of the company's internal control principles. To establish a petty cash fund, a good arrangement in petty cash management is needed, one of which is by making a petty cash fund application form and proof of receipt of petty cash funds. This form is submitted if the petty cash balance is running low or even the balance has run out. The main purpose of using the petty cash fund application form and the petty cash fund receipt form is to carry out internal control over the company's cash. Based on the results of observations at PT. Citra Warna Jaya Abadi found a petty cash fund management system in the company PT. The image of Warna Jaya Abadi is not well organized so that the company's operations are hampered because the petty cash factor used for company operations runs out. In addition, the funds needed for operations are the main benchmark in carrying out company operations for punctuality in completing the specified targets and will be accountable to the leadership. Seeing these conditions, community service at Mahasaraswati Denpasar University is here with a mission to help companies so that the management of petty cash funds is well organized and efficient.